The future of Romanian tourism after COVID 19 pandemic - Elisabeta Roşu; Dan-Marius Voicilaş (Agrarian Economy and Rural Development - Trends and Challenges. International Symposium. 13th Edition, 2022)
The present paper aims to analyse the evolution of tourism activity in Romania, in the period 2010-2021, focusing on the analysis of the effects that the COVID 19 pandemic has had on the Romanian tourism. To reach this objective, a set of indicators were analysed, such as tourism supply, tourist circulation and the supplydemand relationship. The analysis was conducted at national level, for the most important tourist receival structures, and for the number of tourist arrivals and overnight stays, both Romanian and foreign tourists were considered, using data from the national official statistics. The main conclusions of the study indicate that the COVID 19 pandemic has modified tourists' behaviour. This has had an important impact on the sector, reducing tourist flows, resulting in a low degree of occupancy of tourist structures, with a lower impact on those located in the rural area, in the middle of nature, namely tourist and agro-tourist boarding houses, which can be considered the "survivors" of the recent period.
Keywords: Z30; L83; 330; tourism; Romania; COVID 19 pandemic; agro-tourist boarding houses